UNDERSTANDING EFL TEACHERS’ BELIEFS ABOUT LESSON STUDY AND THEIR KNOWLEDGE DEVELOPMENT VIEWED FROM SOCIAL CULTURAL THEORY OF VYGOTSKY - Purwanti, Eko; Hatmanto, Endro Dwi (English Language Teaching Educational Journal, 2019)
Lesson study has been implemented in Indonesian classrooms since more than a decade ago, and it is seen as a means to improve teacher knowledge. This study aims to investigate secondary English teachers? opinions about lesson study in relation to their knowledge development viewed from the lens of Social Cultural Theory of Vygotsky. Using a descriptive qualitative design, the study involved twelve secondary English teachers from two different cities as the participants. In collecting the data from the participants, group interviews were used. The findings showed that most of the participants developed their teaching capacity, particularly in terms of English language knowledge, teaching pedagogy, and teaching innovation. This implies that lesson study is worth to be conducted in different contexts of teaching and learning process.